Near-ground-state cooling in electromechanics using measurement-based feedback and a Josephson traveling-wave parametric amplifier - Rej, Ewa; Cutting, Richa; Depellette, Joe; Datta, Debopam; Tiencken, Nils; Govenius, Joonas; Vesterinen, Visa; Liu, Yulong; Sillanpää, Mika A. (American Physical Society, 2025)
Feedback-based control of nano- and micromechanical resonators can enable the study of macroscopic quantum phenomena and also sensitive force measurements. Here, we demonstrate the feedback cooling of a low-loss and high-stress macroscopic SiN membrane resonator close to its quantum ground state. We use the microwave optomechanical platform, where the resonator is coupled to a microwave cavity. The experiment utilizes a Josephson traveling-wave parametric amplifier, which is nearly quantum-limited in added noise, and is important for mitigating resonator heating due to system noise in the feedback loop. We reach a thermal phonon number as low as 1.6, which is limited primarily by microwave-induced heating. We also discuss the sideband asymmetry observed when a weak microwave tone for independent readout is applied in addition to other tones used for the cooling. In a typical situation, the asymmetry can be attributed to the quantum-mechanical imbalance between emission and absorption. In specific situations, however, we find that the asymmetry is an artifact due to coupling of different sideband processes by cavity nonlinearity under multitone irradiation.
Publisher Copyright: © 2025 American Physical Society. | openaire: EC/H2020/101019712/EU//GUANTUM | openaire: EC/H2020/824109/EU//EMP